The Human Right to Peace: A Legislative Initiative from the Spanish Civil Society (Spanish Yearbook of International Law, 2011)
The article reviews civil society initiatives to codify the human right to peace. The SSIHRL activities in this field (2005–2010) were crucial to disclose the official codification and progressive development process undertaken since 2010 by the United Nations, in particular within the Human Rights Council and its Advisory Committee. It is expected that the General Assembly will approve a Universal Declaration on the Human Right to Peace that should take into account the Santiago Declaration on the Human Right to Peace, as adopted by international civil society on 10 December 2010, as well as its preparatory work.